Absolute and relative grip strength as predictors of cancer: prospective cohort study of 445 552 participants in UK Biobank. Issue 1 (24th December 2021) - Parra‐Soto, Solange; Pell, Jill P.; Celis‐Morales, Carlos; Ho, Frederick K.
Abstract: Background: Reduced muscular strength, as measured by absolute grip strength, has been associated with increased risk of some site‐specific cancers. The ability of grip strength to predict other diseases may be affected by whether it is expressed in absolute or relative terms, but the evidence for cancer is scarce. This study compared the associations of absolute and relative grip strength with all‐cause and 15 site‐specific cancers. Methods: A prospective cohort study was undertaken using data from the UK Biobank. The exposure variable was grip strength, in absolute form (kilogrammes) and relative to weight, body mass index (BMI), height. and body fat mass. The outcome was incident cancer, at 15 sites and overall. Cox proportional hazard models were performed to study the associations. Results: This study included 445 552 participants, where 53.8% of the participants were women, with a mean (SD) age of 56.3 (8.11) years. During a median of 8.8 years follow‐up period, 48 886 (11.0%) patients were diagnosed with cancer. After adjusting for sociodemographic and lifestyle factors, as well as multiple testing, absolute grip strength was inversely and linearly associated with endometrial [hazard ratio (HR): 0.74, 95% confidence interval (CI): 0.69; 0.79, P value <0.001], gallbladder (HR: 0.81, 95% CI: 0.72; 0.92, P value = 0.001), liver (HR: 0.86, 95% CI: 0.79; 0.93, P value <0.001), kidney (HR: 0.93, 95% CI: 0.88; 0.99), and breast (HR: 0.93, 95% CI: 0.91; 0.96, P value = 0.031), as well as all‐cause cancer (HR: 0.97, 95% CI: 0.95; 0.98, P value <0.001). Eight cancer sites were inversely associated with HGS relative to weight and BMI: endometrium, liver, gallbladder, kidney, oesophagus, pancreas, colorectal, breast, and all‐cause cancer. Compared with absolute grip strength, grip strength relative to body fat mass had better discriminatory power for head and neck and breast cancer. Grip strength relative to BMI was marginally better than absolute grip strength in predicting stomach cancer. Conclusions: Grip strength was associated with risk of several site‐specific cancers and all‐cause cancer. Head and neck and breast cancers might be better predicted by relative grip strength.